Próg rentowności a strategiczny cel przedsiębiorstwa - Nita, Bartłomiej (Break-Even and a Corporate Strategic Objective, 2005)
Management accounting refers to the provision of appropriate information for decision making, planning and control within the organization. Traditional techniques involve cost-volume-profit analysis, measuring cost and revenues for decision making and pricing decisions. These instruments very often fail to capture the importance of shareholder value. The paper discusses strategic management accounting and in particular focuses on break-even analysis which needs to be linked with value analysis. Break-even analysis is the core technique for understanding the point at which the business is making an accounting profit. However, one must remember that businesses "breaking-even" are falling short of achieving a rate of return greater than the cost of capital. So, it is possible that a break-even business (like in the example) is still destroying shareholder value. Therefore, the article presents how to figure out the number of products that must be produced and sold in order to satisfy shareholders. In other words we are interested in establishing such quantity of goods that allows achieving the profit equal to the expected profit. Any quantity of goods produced and sold below this point results in the destruction of shareholder value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 274-283